2018
DOI: 10.1177/1054773818773364
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Barriers to Adherence to Hemodialysis Dietary Recommendations

Abstract: Barriers to following dietary recommendations have been described; however, they remain poorly understood. The purpose of this qualitative study was to explore perceived barriers to adherence to dietary recommendations in a diverse hemodialysis patient population. Participants were eligible to participate in a semi-structured qualitative telephone interview prior to randomization for an ongoing clinical trial to evaluate the efficacy of an intervention designed to reduce dietary sodium intake. Interviews were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 50 publications
1
29
0
Order By: Relevance
“…DOPPS Phases 1–3 found that HD patients with poor social support were more likely to experience serum albumin <3.5 g/dL (OR = 1.18, 95% CI: 1.02–1.37) [ 201 ]. In contrast, HD patients with social support achieved better social interactions and coping mechanisms toward kidney disease [ 202 ], as well as fewer depression symptoms [ 208 ]. Ultimately, presence of social support enables patient self-efficacy to reach better health status.…”
Section: Non-iatrogenic Causes Of Malnutritionmentioning
confidence: 99%
“…DOPPS Phases 1–3 found that HD patients with poor social support were more likely to experience serum albumin <3.5 g/dL (OR = 1.18, 95% CI: 1.02–1.37) [ 201 ]. In contrast, HD patients with social support achieved better social interactions and coping mechanisms toward kidney disease [ 202 ], as well as fewer depression symptoms [ 208 ]. Ultimately, presence of social support enables patient self-efficacy to reach better health status.…”
Section: Non-iatrogenic Causes Of Malnutritionmentioning
confidence: 99%
“…Cultural differences in adherence likely contributed to the lower adherence and more modest results compared to the Izmir group, as high‐sodium foods are present in both countries 43 . Furthermore, there are numerous barriers to low‐sodium dietary adherence in the United States that have previously been reported 14–17 . The home‐delivered meal approach used in the current study may be a more efficacious approach for reducing sodium intake, especially in patients with higher IDWG's, because it bypasses many of the barriers upon following a low‐sodium diet or other renal diet restrictions.…”
Section: Discussionmentioning
confidence: 92%
“…43 Furthermore, there are numerous barriers to low-sodium dietary adherence in the United States that have previously been reported. [14][15][16][17] The home-delivered meal approach used in the current study may be a more efficacious approach for reducing sodium intake, especially in patients with higher IDWG's, because it bypasses many of the barriers upon following a low-sodium diet or other renal diet restrictions. However, cost considerations should be taken into account for provision of these meals ($6.99 per renal meal; $587 per patient in this study).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations